Aging and Direct-to-Consumer Prescription Drug Television Ads: The Effects of Individual Differences and Risk Presentation. Issue 4 (3rd April 2019) - O'Donoghue, Amie C.; Johnson, Mihaela; Sullivan, Helen W.; Parvanta, Sarah; Ray, Sarah; Southwell, Brian G.
Abstract : To determine how individual difference (age, cognition, and hearing) and risk presentation (audio frequency, speed, and organization) variables affect viewing of direct-to-consumer (DTC) prescription drug television ads, participants ( N = 1, 075) from four age groups across the adult lifespan took an in-person hearing examination, watched a DTC television ad, and responded to survey questions. Results showed that increased age was related to reduced cognition and hearing ability, as well as lower ad comprehension and risk recall. Greater speed and more complex organization of the ad's risk information lowered risk recall and claim recognition. Audio frequency had no effect. Cognitive abilities mediated the relationship between age and risk recall. Our findings suggest that older adults are likely to have more difficulty recalling and understanding the risks presented in DTC television ads. Risk information can be presented in ways that facilitate or inhibit recall and recognition among individuals across the lifespan.